Eco-Brick-Making Workshop for Cianjur Disaster Survivors - Mukti Utama; Sri Mulyani Nasution; Dody Faraitody T; Asep Deden Rahmat S; Lelly Anggraeni (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The earthquake that rocked Cianjur on November 21 2022 with a magnitude of 5.6 caused around 58,000 residents to be forced to flee. The large number of evacuees and volunteers has caused a pile of garbage at the evacuation site. Seeing this fact, the Faculty of Psychology, Jayabaya University, in collaboration with Putra Indonesia Cianjur University, took the initiative to provide education and training in making eco-brick from used plastic drink bottles. Eco-brick is an easy and inexpensive way to reduce plastic waste that is difficult to decompose. The activity was carried out at MTSN 6 Cianjur on December 28, 2022. From this training, it is hoped that the community will have the ability to utilize waste bottled drinks in goods that have high economic value. Eco-bricks can be used as chairs, tables and even building additives. This activity is also a form of application of environmental psychology as a branch of psychology that studies the interrelationships between individuals and the physical environment, both the natural environment and the human-built environment; set an example and increase public awareness and concern to always maintain the cleanliness of the surrounding environment under any circumstances.